The Biomechanical Stability of Distal Clavicle Excision Versus Symmetric Acromioclavicular Joint Resection. (February 2013) - Pandhi, Nikhil G.; Esquivel, Amanda O.; Hanna, Jason D.; Lemos, David W.; Staron, Jeffrey S.; Lemos, Stephen E.
Background: Treatment for acromioclavicular (AC) joint pain may include distal clavicle excision (DCE). It is possible that DCE can disrupt the surrounding ligaments, leading to increased AC joint laxity. Purpose: To determine the load to failure and stiffness of the AC joint after DCE and symmetric acromioclavicular joint resection (ACJR). Study Design: Controlled laboratory study. Methods: Specimens were randomly assigned to 1 of 2 groups: 1-cm DCE (n = 10) or symmetric (5-mm excision of acromion and distal clavicle) ACJR (n = 10). The specimens were loaded intact in the anterior-posterior plane to determine anteroposterior translation. This was repeated after surgery and compared. The specimens were loaded at 2 mm/s until clinical failure. Force and displacement were recorded, and stiffness was calculated. Results: The peak load to failure for the DCE group was 387.8 N (standard error of the mean [SEM], 31.4 N) and for the ACJR group was 468.5 N (SEM, 30.9 N) ( P = .035). The average stiffness for the DCE group was 35.2 N/mm (SEM, 2.5 N/mm) and for the ACJR group was 37.4 N/mm (SEM, 2.3 N/mm) ( P = .11). There was no significant difference in the anteroposterior translation before and after resection for either group ( P > .05). Conclusion: This cadaveric study demonstrates that the anterior-posterior load to clinical failure of the AC joint after 5 mm of resection from the distal clavicle and medial acromion is significantly greater than 1 cm of the resected distal clavicle alone. Clinical Relevance: Performing ACJR may improve joint stability, leading to fewer complications when compared with DCE.